Specific features of obtaining and using electronic evidence in criminal proceedings - Teslenko, I. O.; Тесленко, І. О. (Право і безпека. - 2024. - № 1 (92). - С. 186-193, 2024)
Проаналізовано точки зору науковців щодо тлумачення поняття електронних доказів; наведено законодавче трактування цього терміна (на відміну від Кримінального процесуального кодексу України в інших процесуальних кодексах закріплено поняття електронних доказів); досліджено судову практику з питань визнання електронних доказів допустимими/недопустимими; виділено основні ознаки електронних доказів. Зважаючи на щоденне вчинення російською федерацією на території України воєнних злочинів, констатовано необхідність збирання та фіксації доказової інформації щодо таких злочинів із відкритих джерел, що в подальшому забезпечить притягнення винних осіб до кримінальної відповідальності.

The relevance and importance of this research is due to the fact that scientific and technological progress and rapid development of information technology in all spheres of public life have significantly influenced the emergence of new types of criminal offences. Criminals are using computer systems and other portable devices to commit unlawful acts with increasing frequency. Today, many criminal offences are being committed with the help of information technology around the world, ranging from simple online fraud to the threat of a territorial act. Therefore, one of the ways to record (document) such illegal activities effectively is to obtain (collect) electronic evidence by law enforcement agencies in criminal proceedings. In this regard, the key role is played by evidence, which helps to form an evidence base that makes it possible to notify a person of suspicion, send an indictment to the court and make a final court decision on the guilt (innocence) of a person in committing a particular criminal offence. Achievement of this objective undoubtedly necessitates a specific legal procedure for seizure of electronic evidence in criminal proceedings, which is not yet clearly defined in terms of its collection, leading to numerous cases of courts declaring such evidence inadmissible. In the course of the scientific research, the author of the article analyses the views of scholars on the interpretation of the concept of electronic evidence; provides the legislative interpretation of this term (unlike the CPC of Ukraine, other procedural codes enshrine the concept of electronic evidence); studies the case law on the issue of electronic evidence being admissible/inadmissible; and identifies the main features of electronic evidence, etc. Given the fact that the Russian Federation commits war crimes on the territory of Ukraine on a daily basis, the author states the need to collect and record evidence of such crimes from open sources, which will further ensure the prosecution of the perpetrators. In the course of studying the specific features of obtaining and using electronic evidence in criminal proceedings, the author applied general scientific and special scientific methods, in particular, dialectical, formal and logical, and comparative legal methods. The interrelated use of these methods allowed for a comprehensive study, where each of these methods was used at a certain stage of the examination of the specific features of obtaining and using electronic evidence in criminal proceedings.

Проанализированы точки зрения ученых по толкованию понятия электронных доказательств; приведена законодательная трактовка этого термина (в отличие от Уголовного процессуального кодекса Украины в других процессуальных кодексах закреплено понятие электронных доказательств); исследована судебная практика по вопросам признания электронных доказательств допустимыми/недопустимыми; выделены основные признаки электронных доказательств. Учитывая ежедневное совершение российской федерацией на территории Украины военных преступлений, констатирована необходимость сбора и фиксации доказательной информации о таких преступлениях из открытых источников, что в дальнейшем обеспечит привлечение виновных к уголовной ответственности.
Особливості отримання та використання електронних доказів у кримінальному провадженні
Keywords: процес доказування; отримання (збирання) доказів; джерела доказів; електронні докази; цифровізація; збирання доказів із відкритих джерел; кримінальне провадження; process of proof; obtaining (collecting) evidence; sources of evidence; electronic evidence; digitalisation; collecting evidence from open sources; criminal proceedings; процесс доказывания; получение (сбор) доказательств; источники доказательств; электронные доказательства; цифровизация; сбор доказательств из открытых источников; уголовное производство